Gaidropsarus granti from a Ligurian seamount: a Mediterranean native species?. (16th October 2013) - Orsi Relini, Lidia; Relini, Giulio
Abstract: Two specimens of the Azorean rockling Gaidropsarus granti (Regan 1903) were caught in the period August 1989–January 1990 on a seamount located about 29 nautical miles south of Genoa, Ligurian Sea. The records remained unpublished because of errors in the literature concerning the two Macaronesian species Gaidropsarus granti and Gaidropsarus guttatus . Old and recent records of G. granti are now used to characterize morphological and ecological traits of this species. In particular, G. granti is unmistakably adapted to a sedentary life on hard substrata, and all records occurred in offshore slope waters, frequently on banks and seamounts. Ecological characteristics and biogeographical considerations are introduced in the discussion about the origin of the Mediterranean records of G. granti, specifically whether this fish should be considered an introduced or a native species.